Syntheses, structures and properties of three chiral metal–organic coordination polymers based on (R)-4-(4-(1-carboxyethoxy)phenoxy)-3-nitrobenzoic acid. (15th July 2018) - Hao, Peng; Huang, Qi; Gu, Lei; Yu, Ying-Hui; Ma, Dong-Sheng
Graphical abstract: Three isomorphic chiral coordination polymers (CCPs), namely, [Co(L)(bimb)] (1 ), [Cd(L)(bimb)] (2 ), [Zn(L)(bimb)] (3 ), (L = (R)-4-(4-(1-carboxyethoxy)phenoxy)-3-nitrobenzoic acid; bimb = 4, 4′-bis((1H-imidazol-1-yl)methyl)-1, 1′-biphenyl) were obtained by solvent thermal method, showing different properties on Fe 3+ ion sensing and catalytic degradation of methylene blue. Abstract: Three chiral metal–organic coordination polymers (CCPs) [Co(L)(bimb)] (1 ), [Cd(L)(bimb)] (2 ), [Zn(L)(bimb)] (3 ), (L = (R)-4-(4-(1-carboxyethoxy)phenoxy)-3-nitrobenzoic acid; bimb = 4, 4′-bis((1H-imidazol-1-yl)methyl)-1, 1′-biphenyl) have been successfully obtained via solvothermal reactions. The isomorphic 2D sq1 type network structures of CCPs 1 –3 were determined by single-crystal X-ray diffraction analysis and further characterized by elemental analyses, IR, PXRD, TGA and circular dichroism (CD) spectra. Crystallized in chiral space group, CCPs 1 –3 exhibit obvious Cotton effects in CD spectra and are proved to be second-harmonic generation (SHG) active. CCPs 1 –3 also exhibit luminescence properties, the intensities of which could be affected by some metal cations, especially Fe 3+ . The Fe 3+ sensing and photo catalytic properties toward methylene blue (MB) were also studied.